(untitled) (Research, Society and Development, 2021)
The aim of this study was to determine the prevalence of Patients with Special Needs seen at the pediatric outpatient clinic of a type III CEO.Method: Descriptive cross-sectional study carried out by surveying 1,384 clinical records of patients from 0 to 19 years of age, with confirmed diagnoses of some special need and attended from June to September 2018. Information collected from medical records such as: the registration number, sex, age, origin, the type of special needs and the history of caries experience. Then, the classification was applied according to the diagnosed pathology, elaborated by Santos & Haddad. Results: Most patients were male (58.2%) and lived in the Metropolitan Region of Recife (51.4%). Regarding special needs, it was found that the highest percentages correspond to patients with Congenital Defects (27.4%), Chronic Systemic Diseases (21.1%), Special Physiological States (15.2%), Physical Defects (14, 7%), Sensory and Audio-communication Defects (8.5%), Behavioral Deviations (4.8%), Intelligence Deviations (4.3%), Endocrine-Metabolic Diseases (3.6%) and Deviations Psychic (0.2%).